Breastfeeding Duration and Authoritative Feeding Practices in First-Time Mothers. (August 2016) - Jansen, Elena; Mallan, Kimberley M.; Byrne, Rebecca; Daniels, Lynne A.; Nicholson, Jan M.
Background: Longer breastfeeding duration appears to have a protective effect against childhood obesity. This effect may be partially mediated by maternal feeding practices during the first years of life. However, the few studies that have examined links between breastfeeding duration and subsequent feeding practices have yielded conflicting results. Objective: Using a large sample of first-time mothers and a newly validated, comprehensive measure of maternal feeding (the Feeding Practices and Structure Questionnaire), this study examined associations between breastfeeding duration and maternal feeding practices at child age 24 months. Methods: Mothers (n = 458) enrolled in the NOURISH trial provided data on breastfeeding at child age 4, 14, and 24 months, and on feeding practices at 24 months. Structural equation modeling was used to examine associations between breastfeeding duration and 5 nonresponsive and 4 structure-related "authoritative" feeding practices, adjusting for a range of maternal and child characteristics. Results: The model showed acceptable fit (χ 2 /df = 1.68; root mean square error of approximation = .04, comparative fit index = .91, and Tucker-Lewis index = .89) and longer breastfeeding duration was negatively associated with 4 out of 5 nonresponsive feeding practices and positively associated with 3 out of 4 structure-related feeding practices. Overall, these results suggest that mothers who breastfeed longer reported using more appropriate feeding practices. Conclusion: These data demonstrate an association between longer breastfeeding duration and authoritative feeding practices characterized by responsiveness and structure, which may partly account for the apparent protective effect of breastfeeding on childhood obesity.